Survival impact based on hepatic artery lymph node status in pancreatic adenocarcinoma: A study of patients receiving modern chemotherapy. Issue 2 (6th November 2020) - Perlmutter, Breanna C.; Hossain, Mir Shanaz; Naples, Robert; Tu, Chao; Vilchez, Valery; McMichael, John; Tullio, Katherine; Simon, Robert; Walsh, R. Matthew; Augustin, Toms
Abstract: Background: Chemotherapy for pancreatic adenocarcinoma (PDAC) has significantly improved in recent years. While the involvement of the hepatic artery lymph node (HALN; station 8a lymph node) likely represents advanced disease, a comparison to patients with metastases on modern chemotherapy is lacking. Methods: Patients who underwent pancreatoduodenectomy with HALN sent for pathologic review at a single institution from 2003 to 2018 were reviewed. Patients who presented with liver‐only metastases at the time of PDAC diagnosis (Stage IV) and received chemotherapy were identified. Multivariate Cox proportional hazards regression modeling was utilized and overall survival (OS) was estimated using Kaplan–Meier analysis. Results: Of the 112 patients with a HALN sent for analysis, 17 (15%) were positive and 13 (76%) received chemotherapy. Ninety‐four stage IV patients were identified and were significantly more likely to have received a multiagent rather than single‐agent chemotherapy regimen compared to HALN positive patients (79.8% vs. 38.5%, p < .001). Median OS was significantly longer in all patients who underwent surgical resection, regardless of HALN status, compared to stage IV patients. Conclusions: Patients undergoing pancreatoduodenectomy with HALN positivity have significantly improved OS compared to patients with stage IV disease. HALN involvement does not significantly alter survival among resected patients and does not warrant preoperative endoscopic ultrasound‐guided biopsy.